Multimodal porous and nitrogen-functionalized electrode based on graphite felt modified with carbonized porous polymer skin layer for all-vanadium redox flow battery. (March 2019) - Yang, Dae-Soo; Han, Jae Hee; Jeon, Jun Woo; Lee, Jang Yong; Kim, Dong-Gyun; Seo, Dong Hack; Kim, Byoung Gak; Kim, Tae-Ho; Hong, Young Taik
Abstract: Novel nitrogen-functionalized multimodal porous graphite felt (GF) electrodes for all-vanadium redox flow batteries (VRFB) have been developed using a simple binder-free fabrication method. We synergistically combined a polymer of intrinsic microporosity (PIM), as a carbon and nitrogen precursor, with vapor-induced phase separation. The GF with a carbonized PIM skin layer showed a high surface area and multimodal pore architecture featuring interconnected micro-, meso-, and macropores. The enhanced electrochemical reactivity and wettability, and excellent electronic conductivity of the prepared electrodes successfully improved the overall kinetics of the redox reactions of the vanadium ion species by providing highly active catalytic sites and efficient ion and electron transport pathways. This resulted in the outstanding performance of VRFB single cells using this material as electrodes. Graphical abstract: Image 1 Highlights: A new strategy for creating porous electrocatalytic skin layer on the carbon felt. Multimodal N-doped carbon electrode with interconnected micro-, meso-, and macropores. Large surface area, excellent wettability, and outstanding electrocatalytic activity. High energy efficiency and rate capability in vanadium redox flow battery.